Inovasi Produk Hygenic di Masa Pandemi Covid-19 - Sukandi, Pipin; Pratama, Huda Mulia Arya (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This research aims to determine the use of hygienic innovation products in people who carry out daily activities during the covid-19 pandemic. This research uses a qualitative method to find out how big the level of difference of hygienic products benefits from other competitors in overcoming people's daily problems in carrying out their activities during the covid-19 pandemic. Based on the results of the research, in terms of the aspect of hygienic products, it can be concluded that that these products can help the community; therefore, innovation in hygienic products has different benefits from its competitors. The difference between this product and its competitors is in the anti-bacterial and skincare substances. With the presence of anti-bacterial substances, this product has different benefits, such as being able to overcome the development of bacteria and viruses that exist in certain body parts that can cause unpleasant odors on the body and clothes. From the business aspect, this product is an innovation that can become a business opportunity in the future because this product has benefits that can overcome simple problems, namely the development of bacteria and viruses on clothing experienced by every member of society in carrying out their productivity activities.